Multiradionuclide evidence for an extreme solar proton event around 2,610 BP (similar to 660 BC) - O'Hare, Paschal; Mekhaldi, Florian; Adolphi, Florian; Raisbeck, Grant; Aldahan, Ala; Anderberg, Emma; Beer, Jürg; Christl, Marcus; id_orcid:0 000-0002-3131-6652; Fahrni, Simon; Synal, Hans-Arno; Park, Junghun; et al. (National Academy of Sciences, 2019)
Recently, it has been confirmed that extreme solar proton events can lead to significantly increased atmospheric production rates of cosmogenic radionuclides. Evidence of such events is recorded in annually resolved natural archives, such as tree rings [carbon-14 (14C)] and ice cores [beryllium-10 (10Be), chlorine-36 (36Cl)]. Here, we show evidence for an extreme solar event around 2,610 years B.P. (∼660 BC) based on high-resolution 10Be data from two Greenland ice cores. Our conclusions are supported by modeled 14C production rates for the same period. Using existing 36Cl ice core data in conjunction with 10Be, we further show that this solar event was characterized by a very hard energy spectrum. These results indicate that the 2,610-years B.P. event was an order of magnitude stronger than any solar event recorded during the instrumental period and comparable with the solar proton event of AD 774/775, the largest solar event known to date. The results illustrate the importance of multiple ice core radionuclide measurements for the reliable identification of short-term production rate increases and the assessment of their origins. ISSN:0027-8424 ISSN:1091-6490